2016
DOI: 10.1149/2.1161614jes
|View full text |Cite
|
Sign up to set email alerts
|

Modification for Improving the Electrochemical Performance of Spherically-Shaped Natural Graphite as Anode Material for Lithium-Ion Batteries

Abstract: A modified spherically-shaped natural graphite (M-SNG) material is prepared, and its physical and electrochemical properties for use as an anode material in lithium-ion batteries are reported. M-SNG is obtained by ultrasonication in a carbon precursor solution, followed by heat-treatment at 1,200°C under argon atmosphere. A gap between the flaky NG fragments forms on the surface and inside the M-SNG particles; amorphous carbon is present in this gap and on the M-SNG particle surface. The M-SNG anode exhibits s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 47 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…NG is known to perform poorly in some cells, which has in the past been attributed to surface exfoliation and cracking of particles. [4][5][6][7] Park et al found spherical natural graphite showed signs of particle swelling and cracking caused by mechanical strain during cycling, which could be suppressed using a carbon coating process. 5 Carbon coatings on natural graphite negative electrodes have been studied in the past to avoid exfoliation from propylene carbonatecontaining electrolytes, but these coatings may decrease the energy density.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NG is known to perform poorly in some cells, which has in the past been attributed to surface exfoliation and cracking of particles. [4][5][6][7] Park et al found spherical natural graphite showed signs of particle swelling and cracking caused by mechanical strain during cycling, which could be suppressed using a carbon coating process. 5 Carbon coatings on natural graphite negative electrodes have been studied in the past to avoid exfoliation from propylene carbonatecontaining electrolytes, but these coatings may decrease the energy density.…”
mentioning
confidence: 99%
“…[4][5][6][7] Park et al found spherical natural graphite showed signs of particle swelling and cracking caused by mechanical strain during cycling, which could be suppressed using a carbon coating process. 5 Carbon coatings on natural graphite negative electrodes have been studied in the past to avoid exfoliation from propylene carbonatecontaining electrolytes, but these coatings may decrease the energy density. 4,6 AG performance reported in the literature appears to outperform natural graphite, however, few direct comparisons of artificial and natural graphite exist in the literature.…”
mentioning
confidence: 99%
“…The SEI layer tends to form mostly during the first cycle, being largely dependent on the specific surface area of the active material [for graphite and G–PD (20 min), specific surface areas are shown in Table S1]. , Therefore, it seems that similar amounts of the SEI layer were generated on all electrodes. However, an irreversible reaction between PD and Li occurred.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, polymeric coating of graphite anode enhanced the cycling stability and decreased the first cycle capacity loss by mitigating electrolyte decomposition at the electrode surface . However, such “add-on solutions” often compromise the primary battery function, i.e., electrochemical energy storage. …”
Section: Introductionmentioning
confidence: 99%